Development of disposable Xanthine Oxidase biosensor for the determination of antioxidant properties of herbal teas - Mohamad Syafiq Sa'odi (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
An enzymatic biosensor has been developed using Xanthine Oxidase (XO enzyme as sensing material for the determination of antioxidant properties of selected herbal teas. The enzyme was immobilized in a Kappa-Carrageenan membrane on a carbon paste electrode. The variables concerning the biosensor preparation such as types of tea, amount of Kappa-Carrageenan membrane, concentration of tea samples, addition of Xanthine solution and tea samples, and also addition of supporting electrolytes were studied. The antioxidant properties of the herbal teas were demonstrated by comparing percentage of inhibition of selected tea samples using the standard 1, 1-diphenyl-2-picrylhydrazyl DPPH free radical scavenging potential and with the cyclic voltammogtram using the Dropsens biosensor. Results show that cyclic voltammetry analysis using the Xanthine Oxidase biosensor produced significant result in comparison with the free radical scavenging activity using DPPH. Even though the results using biosensor is less accurate compared to standard method, but it was fairly acceptable.